Model for the development of specific professional competence in the care of patients with stomatognathic diseases - Ana López Vantour (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Professional competencies are human qualities that allow a personalized vision in an individual, who performs his functions in an unique, and at the same time, changing context, and seeks to develop the personological features that he must use in his working life. Objective: To assess the implementation of a model for the development of specific professional competence in the care of patients with stomatognathic diseases. Methods: A study in medical education was conducted at the Faculty of Dentistry in the University of Medical Sciences from Santiago de Cuba, during the 2018-2019 academic year. The population consisted of the 59 residents who were in the first year of the specialty of Comprehensive General Dentistry, in whom a model for the development of specific professional competence in dental care was applied. During the investigation theoretical and empirical methods were used, as well as statistics, particularly the distribution of absolute and relative frequencies, and McNemar test to evaluate the level of development after the model has been implemented. Results: In the socialization workshop, after the practical implementation of the model, positive opinions were obtained. Among the residents in dentistry, 96.4% approved the relevance of the model, while 83.1% were very satisfied. Conclusions: After applying the proposed model, the development of specific professional competence in the care of patients with dental conditions was evidenced.